Identifikasi Ruang Manuver Menuju Resiliensi Komunitas di Masa Pandemi Covid-19 - Muhammad Nelza Mulki Iqbal; Bayu Teguh Ujianto (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
The pandemic of Covid-19 has hit Indonesia heavily, especially when it was confirmed infectious in early 2020. The government accelerated the immunization program and implemented numerous stimuli and regulations to reduce the effects. However, It didn't stop many people and communities from moving independently to cope with the impacts. An informal community partnership led by Arkom, a community architects’ institution, may be one of the pandemic's resilience efforts. Using a bottom-up and participatory strategy, Arkom has succeeded in building community resilience during the pandemic. The Covid 19 epidemic poses unique challenges from previous physical disasters. Seeing disaster as both a challenge and an opportunity, this study intends to describe Arkom's and its informal community alliances' resilience throughout the COVID-19 pandemic crisis. Safier's room of maneuver lens is used to dismantle scenarios with strategic, technical, organizational, and social components. The data is collected and analyzed using snowball procedures with community members and field facilitators. The study concludes that ARKOM and its community alliances could adapt to make a maneuver during the pandemic, and technology is one of the keys to maneuver success.